Legal Framework of General Visit Visa for Foreign Workers in Indonesia: Kerangka Hukum Visa Kunjungan Umum untuk Pekerja Asing di Indonesia - Islam, Muhammad Alif N; Muis, Lidya Shery (Indonesian Journal of Public Policy Review, 2025)
General Background: The movement of foreign workers across national borders has become increasingly common, requiring countries to regulate their entry and employment. Specific Background: In Indonesia, the implementation of work and visit visas for foreign workers is regulated under Law No. 6 of 2011 on Immigration and Government Regulation No. 34 of 2021. However, the application of these rules reveals inconsistencies in distinguishing between categories of foreign workers. Knowledge Gap: There is still no clear standard or boundary differentiating foreign workers from candidates undergoing work capability trials under the general visit visa scheme. Aims: This research aims to analyze the legal framework, administrative procedures, and regulatory gaps in the use of general visit visas for foreign workers. Results: Findings indicate the absence of explicit standards and overlapping regulations between work visa and visit visa categories, leading to legal uncertainty. Novelty: This study provides a normative legal perspective emphasizing the necessity for regulatory clarity and structured oversight mechanisms. Implications: The study suggests policy reform to establish transparent standards, ensuring lawful and efficient governance of foreign labor practices in Indonesia. Highlights: Unclear standards create regulatory ambiguity. Legal overlap affects labor governance. Calls for clearer visa differentiation policies. Keywords: Visa Policy, Foreign Workers, Immigration Law, Public Policy, Legal Regulation